Vaccine hesitancy and decision regret among nurses in oncology settings in Italy: a cluster-based profile analysis - Rosario Caruso; Pier Mario Perrone; Cristina Arrigoni; Marco Alfredo Arcidiacono; Silvia Belloni; Alice Silvia Brera; Serena Caponetti; Gianluca Conte; Gabriele Cremona; Marcella Dabbene; Monica Guberti; Alessio Piredda; et al. (Scientific Reports)
Abstract Prior studies have examined decision regret and vaccine hesitancy using variable-centered approaches. However, little is known about the diversity of profiles within oncology settings where immunocompromised patients are at high risk. This study aimed to identify distinct clusters of vaccine-related attitudes among Italian nurses working in comprehensive cancer centers. A cross-sectional survey was conducted from June to September 2024, using validated instruments to assess decision regret and vaccine hesitancy (i.e., trust in vaccine efficacy, concerns about vaccine safety, and trust in health authorities and compliance). Data were collected from 241 RNs affiliated with the Italian Association of Cancer Nurses. A t-distributed Stochastic Neighbor Embedding (t-SNE) was used for dimensionality reduction before hierarchical clustering. Seven distinct profiles emerged, ranging from Confident Adherent (low regret, high trust, high compliance) to Resigned Skeptic (low trust, moderate concern, low compliance). Educational status and age significantly influenced cluster membership. Specific profiles displayed unexpected patterns (e.g., high trust with high regret, as in the Regretful Believer group), highlighting the complexity of vaccination attitudes. These findings underscore the importance of person-centered strategies for vaccine communication. Differentiated educational and institutional approaches may enhance trust and adherence among oncology nurses.